Nutrient content evaluation of dried poultry waste urea-molasses block (dpw-umb) on proximate analysis (Faculty of Animal Science, Universitas Brawijaya, 2018)
The research purpose was to determine the nutrient content of dried poultry waste molasses block (DPW-UMB). The use of dried poultry waste in the manufacture of the urea-molasses block was as a substitute of urea and could improve the value added in dry season. The treatments used for research were T1 (15% manure layer chicken and 25% molasses), T2 (10% manure layer chicken and 30% molasses), and T3 (20% manure layer chicken and 30% molasses). Chemical analysis: the dried of poultry waste were analyzed for dry matter, crude protein, crude fiber, ash, fat, and gross energy. The statistical formulation diet composed of Microsoft Excel Ver. 2016. The results showed that the 20% manure layer chicken and 30% molasses (T3) were better than T2 and T1 on nutrient content with 92.04% Dry Matter (DM), 13.34% Crude Protein (CP), 13.39% Crude Fiber (CF), 37.16% ash, 3.44% fat, but low in Gross Energy (GE) (2631.63 kcal/kg). It could be concluded that dpw-umb T3 were dried of poultry waste contained sufficient levels of gross energy, crude protein, crude fiber, ash, and fat it could be used as feedstuff for ruminants for supplementation with the required nutrients.